Monoculture plantations impede forest recovery: Evidence from the regeneration of lowland subtropical forest in Hong Kong - Zhu, Huiling; Zhang, Jinlong; Cheuk, Mang Lung; Hau, Billy C. H.; Fischer, Gunter A.; Gale, Stephan W. (Frontiers in Forests and Global Change, 2023)
Anthropogenic disturbance has led to widespread clearance and degradation of tropical forests, and tree planting has been promoted as an effective solution for recovery. However, trees have been overwhelmingly planted in monocultures or low-diversity mixes and this is expected to have profound, lasting impacts on forest structure, diversity, and functioning. In this study, we tested the extent to which historical vegetation transition types (VTTs) constrain forest recovery in a secondary tropical landscape in Hong Kong, South China. To do so, we overlaid vegetation types (forest, shrubland, pine plantation, grassland) identified in aerial photographs taken in 1956 and 1963 of a 20-ha plot situated in Tai Po Kau Nature Reserve, allowing us to define six historic VTTs, namely: FF (forest to forest), GP (grassland to plantation), GS (grassland to shrubland), SS (shrubland to shrubland), SF (shrubland to forest), and SP (shrubland to plantation). We compared present-day forest structure and species diversity among these VTTs, as determined from a census conducted in 2015, using incidence- and abundance-based rarefaction and extrapolation, and we assessed species’ association within VTTs using a torus translation test. Our results reveal that stem density and species diversity in naturally regenerated forests were more similar to those of old-growth forest, whereas species diversity in areas occupied by pine plantations was significantly lower as compared with naturally regenerated areas. Despite 60 years of recovery, pine plantations were characterised by a significantly greater proportion of negatively associated species, and late-seral species were still predominantly confined to old-growth patches. Present-day species distribution is chiefly explained by the combined effects of topography and VTT (17.1%), with VTT alone explaining 4.4%. Our study demonstrates that VTT has a significant long-term impact on forest regeneration and community assembly and, importantly, that monocultural plantations (forest plantation) can greatly impede forest recovery. Remnant old-growth forest patches merit priority protection, and active restoration, including thinning and enhancement planting, is necessary to facilitate forest succession.